Effect of a compound starter cultures inoculation on bacterial profile and biogenic amine accumulation in Chinese Sichuan sausages - Hongyang Ren; Yuanpeng Deng; Xinhui Wang (Food Science and Human Wellness)
Effects of a starter culture composed of Lactobacillus sakei, Pediococcus pentosaceus, Staphylococcus xylosus and S. carnosus at the ratios (m/m) of 1:1:1:1 on bacterial profile and biogenic amine accumulation in Chinese Sichuan sausages were demonstrated. In starter culture-inoculated sausages, Lactobacillus spp., Pediococcus spp. and Staphylococcus spp. were predominant bacterial genus and their relative abundances ranged from 70.14% to 25.98%, 57.66% to 14.08%, and 15.71% to 13.40% during fermentation, respectively. Accordingly, Lactobacillus spp. and Weissella spp. were predominant bacterial genus and their relative abundances ranged from 63.14% to 24.70% and 49.40% to 11.96% during spontaneous fermentation, respectively. Furthermore, the abundances of undesirable microorganisms such as Yersinia spp., Enterobacter spp., Acietobacter spp. and Psychrobacter spp. were lower than that of the control. The levels of histamine, putrescine, tyramine and cadaverine in Chinese Sichuan sausages with starter cultures inoculation were significantly lower (P < 0.05) than that of the control, and were decreased by 83.09%, 69.38%, 51.87% and 57.20%, respectively, at the end of the ripening. These results revealed that the starter cultures inoculation was a better alternative for microbial quality improvement and biogenic amine reduction of Chinese Sichuan sausages with good sensory attributes.